2021
DOI: 10.1002/erv.2832
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric network structure of mental health in eating disorder patients

Abstract: Objective Psychometric network analysis has led to new possibilities to assess the structure and dynamics of psychiatric disorders. The current study focuses on mental health networks in patients with anorexia nervosa, bulimia nervosa, binge eating disorder and other specified eating disorders (EDs). Method Network analyses were applied with five mental health domains (emotional, psychological and social well‐being, and general and specific psychopathology) among 905 ED patients. Also, networks of 36 underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 69 publications
1
20
0
Order By: Relevance
“…Remarkably, many studies reported no differences in network structure nor in global strength with regards to different ED diagnoses [ 42 , 50 , 61 ], age [ 34 , 35 , 75 ], and sex [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, many studies reported no differences in network structure nor in global strength with regards to different ED diagnoses [ 42 , 50 , 61 ], age [ 34 , 35 , 75 ], and sex [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…In line with the application to other mental disorders, various research goals can be identified among the existing literature about network approaches to EDs, namely: validation of the transdiagnostic model of eating disorders by comparing network characteristics across ED diagnoses (DuBois et al, 2017; Forrest et al, 2018; Goldschmidt et al, 2018; Mares et al, 2021; Monteleone, Tzischinsky, et al, 2022; Solmi et al, 2018; Solmi et al, 2019); estimation of the symptom network of EDs and identification of the core symptoms (Beauchamp et al, 2021; Forbush et al, 2016; Forrest et al, 2018; Forrest, Perkins, et al, 2019; Rodgers et al, 2018; Wang et al, 2019); identification and interaction with nonspecific ED symptoms (i.e., the external field) like general psychiatric symptoms, personality traits and other clinical variables (Monteleone, Mereu, et al, 2019; Solmi et al, 2018; Solmi et al, 2019), embodiment dimensions (Cascino et al, 2019), childhood maltreatment (Liebman et al, 2021; Monteleone, Cascino, et al, 2019; Monteleone, Tzischinsky, et al, 2022; Rodgers et al, 2019), mentalizing and empathy (Monteleone et al, 2020), vulnerability factors (Vervaet et al, 2021), suicidal thoughts and behaviors (Smith et al, 2020), perfectionism and interoceptive sensibility (Martini et al, 2021), affective and metacognitive symptoms (Aloi et al, 2021; Wong et al, 2021), interoceptive awareness (Brown et al, 2020), sleep disturbance (Ralph-Nearman et al, 2021), well-being domains (de Vos et al, 2021), inflexible and biased social interpretations, socioemotional functioning (Bronstein et al, 2022); assessment of psychiatric comorbidities such as depression and anxiety (Bronstein et al, 2022; Elliott et al, 2020; Kenny et al, 2021; Levinson et al, 2017; Sahlan, Williams, et al, 2021; Smith et al, 2019), posttraumatic stress disorder (Liebman et al, 2021; Vanzhula et al, 2019), social anxiety disorder (Levinson et al, 2018a; Sahlan, Keshishian, et al, 2021), obsessive-compulsive disorder (Giles et al, 2022; Kinkel-Ram et al, 2021; Meier et al, 2020; Vanzhula et al, 2021), trait anxiety disorder (Forrest, Sarfan, et al, 2019), autism spectrum disorder (Kerr-Gaffney et al, 2020), borderline personality disorder (De Paoli et al, 2020), and alcohol misuse (Cusack et al, 2021); comparison of estimated network structures among clinical and nonclinical (Vanzhula et al, 2019),...…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, many studies reported no differences in network structure nor in global strength with regards to different ED diagnoses (de Vos et al, 2021; Goldschmidt et al, 2018; Mares et al, 2021), age (Brown et al, 2020; Calugi et al, 2020; Sahlan, Williams, et al, 2021), and sex (Sahlan, Keshishian, et al, 2021; Sahlan, Williams, et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text of the remaining 65 articles and 3 dissertations were assessed, leading to the exclusion of an additional 35 articles. The remaining 33 articles were thus included in the review (Brown et al, 2020;Calugi et al, 2020Calugi et al, , 2021Calugi et al, , 2022Cascino et al, 2019;Chen et al, 2022;de Vos et al, 2021;DuBois et al, 2017;Elliott et al, 2020;Forrest et al, 2018Forrest et al, , 2019Goldschmidt et al, 2018;Hagan et al, 2021;Hilbert et al, 2020;Kerr-Gaffney et al, 2020;Levinson et al, 2017;Mares et al, 2022;Meier et al, 2020;Monteleone et al, 2019Monteleone et al, , 2020Monteleone et al, , 2022Olatunji et al, 2018;Ralph-Nearman et al, 2021;Schlegl et al, 2021;Smith et al, 2019;Smith et al, 2020;Solmi et al, 2018Solmi et al, , 2019Vanzhula et al, 2019;Vervaet et al, 2021;Wang et al, 2019;Wong et al, 2021). See Figure 1 for the flowchart of the selection process, including reasons for exclusion at each step.…”
Section: Selection Of Articles and Study Characteristicsmentioning
confidence: 99%